Periodontitis as a risk for oral cancer: a case-control study - György Komlós; Katalin Csurgay; Ferenc Horváth; Liza Pelyhe; Zsolt Németh (BMC, 2021)
Abstract Background The aetiology of oral cancer is multifactorial, as various risk factors (genetics, socioeconomic and lifestyle factors) contribute to its development. Data in the literature suggest that people with periodontal disease have an increased risk of developing oral cancer, and the severity of periodontitis correlates with the appearance of oral squamous cell carcinoma. The aim of this study was to revise the non-genetic risk factors that may influence the development of OC, while focusing on the dental and periodontal status and OH. Methods Two hundred patients (hundred diagnosed with oral cancer and hundred without oral cancer) were enrolled in our case-control study, to evaluate the association between oral cancer and the presence and severity of periodontitis, while examining several risk factors that might be responsible for oral cancer formation. A questionnaire customised for oral cancer patients was used to obtain the socioeconomic and lifestyle risk factors that may influence the development of oral squamous cell carcinoma. The dental and periodontal status along with the level of oral hygiene was recorded quantitatively. The chi-square and Mann-Whitney tests and logistic regression were used for the statistical analysis. Results By considering both the case and the control groups, a significant correlation was found between the incidence of oral cancer and some socioeconomic factors and lifestyle habits, such as the sex, age, education and alcohol consumption of an individual. The mean value of the Silness-Löe plaque index was significantly higher in the case population. The number of completely edentulous patients was higher among the oral cancer population. The incidence of oral cancer was 57.1% in patients with periodontal disease. In comparison, the incidence of oral squamous cell carcinoma was only 28.6% among the patients without periodontitis. Most of the oral cancer patients (72.1%) had stage 4 periodontitis. On the other hand, the vast majority of the control group (51.6%) had stage 2 periodontitis. Conclusion Periodontitis can be an individual risk factor for oral cancer development. Periodontally compromised individuals should be strictly monitored, especially those with severe periodontitis and coexisting lifestyle risk factors. Maintaining their periodontal health in at-risk patients can minimize cancer risks.